Transmission analysis of candidate genes for nonsyndromic oral clefts in Brazilian parent-child triads with recurrence - da Silva, Aline Loureno̧ [UNESP]; Ribeiro, Lucilene Arilho [UNESP]; Cooper, Margaret E.; Marazita, Mary L.; Moretti-Ferreira, Danilo [UNESP] (FapUNIFESP (SciELO), 2006)
Cleft lip and/or palate (CL/P) is a major congenital defect with complex etiology, including multiple genetic and environmental factors. Approximately two thirds of the cases are not accompanied by other anomalies and are called nonsyndromic (NS). In the present study, we performed transmission distortion analysis of the MSX1-CA, TGFB3-CA and MTHFR-C677T polymorphisms in 60 parent-child triads, in which the NS-CL/ P affected child had at least one affected parent. No association with genes MSX1 or TGFB3 was found, but the results were suggestive of an association of the MTHFR-C677T polymorphism with NS-CL/P. © 2006 Sociedade Brasileira de Genética.
Keywords: Cleft lip; Cleft palate; Oral clefts; 5,10 methylenetetrahydrofolate reductase (FADH2); DNA; transcription factor MSX1; transforming growth factor beta3; adult; allele; child; cleft lip; cleft palate; DNA determination; family assessment; female; gene frequency; gene linkage disequilibrium; gene mapping; genetic association; genetic polymorphism; genetic risk; genotype; heredity; human; major clinical study; male; pathophysiology; risk assessment; sex difference